2012
DOI: 10.1007/s00467-012-2140-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatments and outcomes for end-stage renal disease following Wilms tumor

Abstract: Background Little is known about treatment outcomes for children who have end stage renal disease (ESRD) after treatment for Wilms tumor (WT). Methods Time-to-transplant, graft failure and survival outcomes were examined for 173 children enrolled on the National Wilms Tumor Study who developed ESRD. Results Fifty-five patients whose ESRD resulted from progressive bilateral WT (PBWT) experienced high early mortality from WT that limited their opportunity for transplant (47% at 5 years) and survival (44% at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…14 Another study in nearly 6000 patients with Wilms tumor revealed cumulative risks of renal failure at 20 years from diagnosis in Denys-Drash and Wilms tumor-Aniridia syndromes of 62% and 38%, respectively. 18 In summary, long-term outcomes for children with renal tumor in Thailand may be less favorable, partly because of advance stage at presentation. Patients with bilateral disease had a risk of 6%.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another study in nearly 6000 patients with Wilms tumor revealed cumulative risks of renal failure at 20 years from diagnosis in Denys-Drash and Wilms tumor-Aniridia syndromes of 62% and 38%, respectively. 18 In summary, long-term outcomes for children with renal tumor in Thailand may be less favorable, partly because of advance stage at presentation. Patients with bilateral disease had a risk of 6%.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The refinement of multimodal therapy, which can include surgery, chemotherapy, and radiation therapy, has remarkably improved the outcome of children with renal tumors, with an overall survival rates of 90% in developed countries. [2,3] The treatment of WT is one of the great success stories in oncology; however, certain subgroups of patients still do not fare well, including those with anaplastic histology, bilateral diseases, and recurrent diseases. [4,5] Specifi c challenges are faced in treating children with renal tumors in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of NWTS trials performed by Grigoriev et al (14) showed that ESRD was diagnosed in 173 patients among 9,162 individuals with WT treated between October 1969 and April 2002. The most common causes of ESRD were progressive BWT (55); DDS (27); WAGR syndrome (10); radiation nephritis (12); focal segmental glomerulosclerosis (18); CKD, aetiology unknown (16) and hypertension (7).…”
Section: End-stage Renal Disease In Wtmentioning
confidence: 99%
“…The remaining 118 patients, many of whom had WT1-associated congenital anomalies, had transplant (77% at 5 years) and survival (73% at 10 years) outcomes no worse than those for population controls. The risk of ESRD due to progressive BWT was largely confined to the first 3 years following the onset of bilateral disease, whereas the incidence rates of ESRD due to CKD continued to increase for 20-25 years from WT diagnosis (14).…”
Section: End-stage Renal Disease In Wtmentioning
confidence: 99%